Surfactant Therapy in Premature Infants: A Critical Tool in Neonatal Care - Rustamov Bakhtiyorjon (Scientific Trends, 2025)
Premature birth is a major contributor to neonatal morbidity and mortality, with respiratory distress syndrome (RDS) representing one of the most critical complications. Surfactant therapy has revolutionized the management of RDS in preterm infants, significantly improving survival and reducing pulmonary complications. This article reviews the physiology of surfactant, the pathophysiology of RDS, the types of surfactant preparations available, administration techniques, timing of therapy, and current best practices.
Keywords: Respiratory distress syndrome (RDS), very low birth weight (VLBW), Incidence of Bronchopulmonary Dysplasia (BPD), Oxygen Saturation and Blood Gas Levels, Surfactant proteins (SP-A and SP-D), neonatal intensive care unit (NICU), randomized controlled trial (RCT).